The transition of tissue inhibitor of metalloproteinases from -4 to -1 induces aggressive behavior and poor patient survival in dedifferentiated liposarcoma via YAP/TAZ activation. (10th May 2019) - Shrestha, Madhu; Ando, Toshinori; Chea, Chanbora; Sakamoto, Shinnichi; Nishisaka, Takashi; Ogawa, Ikuko; Miyauchi, Mutsumi; Takata, Takashi
Abstract: Liposarcoma (LS) is the most common soft-tissue sarcoma. Dedifferentiated liposarcoma (DDLS) shows more aggressive biological behavior than that of well-differentiated liposarcoma (WDLS), so advanced therapeutic agents based on molecular mechanism are urgently needed. Here we show that tissue inhibitors of metalloproteinases (TIMPs) from TIMP-1 to TIMP-4 are differently expressed and regulate yes-associated protein (YAP)/transcriptional co-activator with PDZ binding motif (TAZ) in LS. Database analysis showed high TIMP-1 expression in DDLS patients correlating with poor prognosis, but high TIMP-4 expression in WDLS patients with better prognosis. Stable TIMP-1 knockdown inactivated YAP/TAZ and inhibited proliferation, colony formation and migration in DDLS cells, which was rescued by a constitutive active YAP. However, stable overexpression of TIMP-1 showed the opposite in WDLS cells. Stable TIMP-4 knockdown activated YAP/TAZ and promoted proliferation and migration in WDLS cells, which was suppressed by YAP/TAZ inhibitor (verteporfin) or knockdown of YAP/TAZ. Recombinant TIMP-4 showed opposite results in DDLS cells. These results indicate that dedifferentiation in LS shifts the expression of TIMPs from type 4 to type 1, inducing more aggressive behavior and poor prognosis through YAP/TAZ activation, which can be prognostic markers and therapeutic targets for LS patients. Abstract : This article highlights the change in expression of tissue inhibitors of metalloproteinases (TIMPs) from TIMP-4 to TIMP-1 from well-differentiated liposarcoma to a dedifferentiated phenotype, resulting in activation of YAP/TAZ thereby leading to more aggressive biological behaviors such as increased proliferation and migration potential.